Peningkatan Hasil Belajar IPAS Siswa pada Materi Manusia dan Lingkungan melalui Penerapan Metode Picture and Picture Berbantu Media Canva di Kelas V SD Negeri 064966 Medan - Hilda Rahmadani Harahap; Suci Perwita Sari; Lindang Marturasi Pakpahan (MASALIQ, 2025)
Science and Social Studies (IPAS) instruction in elementary schools often tends to be monotonous and lacks the use of visual technology, which hampers active student engagement and negatively affects learning outcomes. This study aims to improve the learning outcomes of fifth-grade students at SD Negeri 064966 Medan on the topic of Humans and Environment through the application of the Picture and Picture method combined with Canva media. The main issues identified were low student engagement and motivation, as well as limited use of engaging and creative instructional media. The research employed Classroom Action Research (CAR) conducted over two cycles, each comprising planning, implementation, observation, and reflection phases, with 27 students as subjects. Data were collected through observations of teacher and student activities and learning outcome tests. The results demonstrated improved instructional quality, with teacher activity scores increasing from an average of 77.17 (good category) in cycle I to 82.50 (good category) in cycle II, while student activity scores rose from 52.5 (fair category) to 85 (very good category). Learning outcomes also showed significant improvement, with mastery rising from 26% in the pre-action phase to 52% in cycle I and reaching 89% in cycle II. In conclusion, the application of the Picture and Picture method assisted by Canva media is effective in enhancing both student engagement and learning outcomes on the topic of Humans and Environment.